Penerapan Model Pembelajaran Multiple Intelligences pada Pembelajaran Tahsin di SMAIT Miftahul Khoir Kota Bandung - Nur Amalia Aini Sidik; Helmi Aziz; Ikin Asikin (UNISBA Press, 2022)
Abstract. In this increasingly modern era, many think that just reading the Qur'an is enough. So that many people can read the Qur'an, but there are still many mistakes from reading it if you look at it from the side of recitation. This causes several problems regarding the lack of ability to read the Qur'an of students properly and in accordance with the rules of tajwid and also the makharijul letters. The Tahsin learning program using the multiple intelligences application model carried out by SMA-IT Miftahul Khoir Bandung City is an effort made by teachers to improve the ability to read the Qur'an by placing students according to their abilities. This study aims to determine the planning, implementation, evaluation, advantages and limitations of the Tahsin program with the application of the multiple intelligences learning model in Tahsin learning at SMA-IT Miftahul Khoir Bandung City. The method used in this study is a descriptive qualitative method. The type of data used is qualitative data. In terms of collecting data, the researcher used observation, interview, and documentation studies. While the data analysis techniques used are through, reduction, data presentation, triangulation and drawing conclusions (verification). The results of this study generally indicate that the Tahsin program with the application of the multiple intelligences learning model in Tahsin learning at SMA-IT Miftahul Khoir Bandung City, which is carried out regularly, has brought significant results to students. These changes can be seen from the number of students who have good progress in terms of reading the Koran, it's just that there are still some students who have difficulty due to their own laziness. Abstrak. Di era yang semakin modern ini, banyak yang beranggapan bahwa membaca Al-Qur'an saja sudah cukup. Agar banyak orang yang bisa membaca Al-Qur'an, namun masih banyak kesalahan dari membacanya jika dilihat dari sisi bacaannya. Hal ini menyebabkan beberapa permasalahan mengenai kurangnya kemampuan membaca Al-Qur'an siswa dengan baik dan sesuai dengan kaidah tajwid dan juga huruf makharijul. Program pembelajaran Tahsin dengan menggunakan model aplikasi multiple intelligences yang dilakukan oleh SMA-IT Miftahul Khoir Kota Bandung merupakan upaya yang dilakukan oleh guru untuk meningkatkan kemampuan membaca Al-Qur’an dengan menempatkan siswa sesuai dengan kemampuannya. Penelitian ini bertujuan untuk mengetahui perencanaan, pelaksanaan, evaluasi, kelebihan dan keterbatasan program Tahsin dengan penerapan model pembelajaran multiple intelligences dalam pembelajaran Tahsin di SMA-IT Miftahul Khoir Kota Bandung. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Jenis data yang digunakan adalah data kualitatif. Dalam pengumpulan data, peneliti menggunakan observasi, wawancara, dan studi dokumentasi. Sedangkan teknik analisis data yang digunakan adalah melalui, reduksi, penyajian data, triangulasi dan penarikan kesimpulan (verifikasi). Hasil penelitian ini secara umum menunjukkan bahwa program Tahsin dengan penerapan model pembelajaran multiple intelligences dalam pembelajaran Tahsin di SMA-IT Miftahul Khoir Kota Bandung yang dilaksanakan secara rutin telah membawa hasil yang signifikan bagi siswa. Perubahan tersebut terlihat dari banyaknya siswa yang memiliki kemajuan yang baik dalam hal membaca Alquran, hanya saja masih ada beberapa siswa yang mengalami kesulitan karena kemalasannya sendiri.